2010
DOI: 10.3357/asem.2786.2010
|View full text |Cite
|
Sign up to set email alerts
|

Brain MRI Signal Abnormalities and Right-to-Left Shunting in Asymptomatic Military Divers

Abstract: Healthy military divers with a hemodynamically relevant RLS have an increased likelihood of cerebral hyperintense spots compared to age-matched normal subjects. The clinical relevance of these MRI signal abnormalities and their causal relationship with diving remain unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Several previous studies reported imaging findings associated with NDCS in high-altitude mountain climbing (1,12) and deep sea divers (11,15). High-altitude mountain climbers have been reported as having an increased preponderance of subcortical HWM lesions and enlarged Virchow-Robin spaces relative to normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies reported imaging findings associated with NDCS in high-altitude mountain climbing (1,12) and deep sea divers (11,15). High-altitude mountain climbers have been reported as having an increased preponderance of subcortical HWM lesions and enlarged Virchow-Robin spaces relative to normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…46 Historically, in asymptomatic divers, brain MRI scanning in some studies suggested increased white matter lesions in association with right-to-left shunting. 47,48 This has not been confirmed in all studies, however. 49,50 One study showed 29% of divers with a PFO suffering major decompression illness versus 6% without ( P = 0.016), with a further association between the size of PFO and decompression illness lasting longer than 24 hours.…”
Section: Indications For Pfo Closurementioning
confidence: 75%
“…Arterialized gas emboli have been considered one of the main causes of decompression-related pathology. Recently, Gempp et al demonstrated that the proportion of hyperintense spots in compressed-air divers was closely related to the presence of a large RLS [16], as suggested by Knauth et al [17]. The presence of RLSs in divers is an important risk factor in cerebral DCI events.…”
Section: Discussionmentioning
confidence: 92%